Limited Adherence to Peripheral Arterial Disease Guidelines and Suboptimal Ankle Brachial Index Reliability in Dutch Primary Care. (June 2018) - Hageman, David; Pesser, Niels; Gommans, Lindy N.M.; Willigendael, Edith M.; van Sambeek, Marc R.H.M.; Huijbers, Ellen; Snoeijen, Aafke; Scheltinga, Marc R.M.; Teijink, Joep A.W.
Abstract : Objective/Background: The Dutch College of General Practitioners' guideline on peripheral arterial disease (PAD) provides clear recommendations on the management of PAD. An ankle brachial index (ABI) measurement, prescription of antiplatelet drugs and statins, and supervised exercise therapy (SET) for intermittent claudication (IC) are advised. The aims of this study were to determine the adherence of general practitioners (GPs) to their own guideline on PAD and to evaluate the reliability of primary care ABI measurements. Methods: This was a cross-sectional study. All patients suspected of having symptomatic PAD who were referred by GPs to a large hospital in 2015 were evaluated regarding three of the guideline criteria: (i) ABI measurement; (ii) prescription of secondary prevention; (iii) initiation of SET. ABI values obtained in primary care and the hospital's vascular laboratory were compared using correlation coefficients and regression analysis. An abnormal ABI was defined as a value <.9 (normal ABI ≥.9). Results: Of 308 potential patients with new onset PAD, 58% ( n = 178) had undergone ABI measurement prior to referral. A modest correlation between ABI values obtained in primary care and the vascular laboratory was found ( r = .63, p < .001). Furthermore, a moderate reliability was calculated (intraclass correlation coefficient 0.60, 95% confidence interval 0.49–0.69, p < .001). Of the new patients with an abnormal ABI, 59% used antiplatelet drugs and 55% used statins. A referral for SET was initiated by a GP in 10% of new PAD patients with IC symptoms. Conclusions: Adherence by Dutch GPs to their own society's PAD guideline has room for improvement. The reliability of ABI measurements is suboptimal, whereas rates of prescription of secondary prevention and initiation of SET as primary treatment for IC need upgrading.